Turmeric: Golden spice to value-added treasure - P V, Alfiya; E, Jayashree; K, Anees (Indian Horticulture, 2025)
Turmeric (Curcuma longa), renowned as the 'golden spice', is gaining global recognition for its culinary, medicinal, and industrial value. Rich in bioactive compounds like curcumin, turmeric exhibits antioxidant, anti-inflammatory, and antimicrobial properties. This paper explores the growing potential of valueaddition in turmeric, from primary processing to tertiary products such as essentialoils, oleoresins, and nutraceuticals. Innovations like freeze-drying and product diversification (e.g., golden milk, turmeric flakes, and cosmetics) enhance shelf life and market appeal.